The Appearance of Economic, Social, Financial and Environmental Sustainability Aspects in the Practices of the National Bank of Hungary - Matolcsy, György (Public Finance Quarterly, 2022)
Sustainability is at the heart of the challenges in the 21st century. Economic, social, financial and environmental sustainability also fundamentally determine the functioning of the economic system, which means that the convergence process, guided by new visions, can only be organised around the idea of sustainability. The revolution in thinking on sustainability has also reached the community of central banks, and the National Bank of Hungary was one of the first central banks to take meaningful steps to integrate environmental sustainability considerations into the regulatory framework of the banking system, reserve management, monetary policy, collateral management and data disclosure. In its strategy documents, the Bank has defined its mission to be an active participant in the transition to a low-carbon economy.